Heat-moisture-treated rice improves oral glucose tolerance by modulating serum and fecal metabolites in mice - Zhang, Jinming; Kong, Aohua; Chen, Xiaomin; Zhang, Mingxue; Xu, Fei; Hu, Shouna; Wang, Jinyu; Xiong, Ke (Frontiers in Nutrition, 2025)
Background/objectiveHeat-moisture treatment (HMT) can increase the composition of resistant starch and reduce the glycemic index in rice. However, the effect of long-term HMT-rice feeding is unknown. The objective is to investigate the effect of long-term HMT-rice feeding on alleviating hyperglycemia in mice and explore potential mechanisms.MethodsIn this study, HMT-rice was characterized for its X-ray diffraction pattern, in-vitro and in-vivo digestibility. In the feeding experiment, thirty C57BL/6 male mice were fed for 3 months using one of the three diets (n = 10 per group): a high-fat diet (HFD, containing untreated rice), an HFD supplemented using HMT-rice, or a control diet. After 3 months, the blood glucose and lipids, body weight and fat, and histopathological changes of liver and colon tissues were measured. Determination of metabolites in serum and feces was conducted by liquid chromatography tandem mass spectrometry. Association between differential serum/fecal metabolites and blood glucose/lipid parameters were determined by Spearman correlation analysis.ResultsThe mice in the HMT-rice group had significantly improved oral glucose tolerance and reduced serum cholesterol and body weight gain versus the HFD group. For serum metabolites, HMT-rice significantly enriched several lysophospholipids. The increase of several fecal metabolites including oxidized phospholipids and bile acid/amino acid derivatives by HFD feeding were significantly reversed by HMT-rice treatment. The changes of these serum and fecal metabolites were correlated with the changes of fasting serum glucose.ConclusionHMT-rice significantly improved oral glucose tolerance in HFD-fed mice through the regulations of serum and fecal metabolites.